2002
DOI: 10.1021/ma0116856
|View full text |Cite
|
Sign up to set email alerts
|

Unique Behavior of Nitroxide Biradicals in the Controlled Radical Polymerization of Styrene

Abstract: The use of various binitroxides, with both radical sites of similar reactivity, as mediator in the controlled radical polymerization of styrene was examined and the rate constants of the reactions involved were determined at 130 °C. Typical features of a controlled radical polymerization were observed in the early stage of the polymerization, leading to the formation of two-arm macromolecules containing the binitroxide at the core. At higher conversion, however, continuous decomposition reaction resulted in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…Both seeded and ab initio emulsion polymerizations of isoprene are carried out to separate the nucleation and particle growth processes in order to explain the previously reported low yield of polyisoprene initiated by redox systems [39,40]. Polystyrene latexes of different diameters (30,65, and 139 nm, measured by photon correlation spectroscopy) were used as seeds, with an oil-soluble initiator couple to reduce the likelihood of secondary particle nucleation. This 'hetero-seeded' polymerization of isoprene in a styrene seed assumes full compatibility between the different species of polymer involved, which should be an adequate approximation at low to moderate conversion [68].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both seeded and ab initio emulsion polymerizations of isoprene are carried out to separate the nucleation and particle growth processes in order to explain the previously reported low yield of polyisoprene initiated by redox systems [39,40]. Polystyrene latexes of different diameters (30,65, and 139 nm, measured by photon correlation spectroscopy) were used as seeds, with an oil-soluble initiator couple to reduce the likelihood of secondary particle nucleation. This 'hetero-seeded' polymerization of isoprene in a styrene seed assumes full compatibility between the different species of polymer involved, which should be an adequate approximation at low to moderate conversion [68].…”
Section: Methodsmentioning
confidence: 99%
“…In this work, benzoyl peroxide (BPO) was used as thermal initiator and TEMPO [64,65] as radical trap. The rate of abstraction by the highly reactive and electrophilic benzoyloxy radical was found to be three times larger than its addition to the internal double bonds of squalene, and the majority of addition was to terminal double bonds, suggesting that hydrogen abstraction is the dominant cross-linking mechanism when polyisoprene is treated with peroxides.…”
Section: Peroxide Cross-linkingmentioning
confidence: 99%
“…1 They also found applications in the fields of dynamic nuclear polarization (DNP) 2 and living free radical polymerization. 3 To date, most stable biradicals consist of two identical radical moieties, but mixed biradicals have also exhibited unique physico-chemical properties and found applications for sensing NO, 4 pH 5 and redox status 6 in biological systems.…”
mentioning
confidence: 99%
“…The molecular weight distributions ranged from 1.30 to 1.59 and were typical of polymerizations mediated with dinitroxides. 38 It was presumed that the relatively broad molecular weight distributions were the result of the lower rate constant of recombination associated with the coupling reaction of a polymeric nitroxide and a propagating polymer radical, as reported by Vairon et al 38 The broadest molecular weight distribution was observed with a 0.10 wt % initiator. This was attributed to an increased relative contribution of initiating radical species resulting from styrene thermal autopolymerization.…”
Section: Dinitroxide-mediated Polymerizations Of Styrenementioning
confidence: 86%
“…A variety of polymer compositions and structures, including star and graft copolymers, have been investigated with SFRP methodologies. [31][32][33][34][35][36][37] The use of a dinitroxide mediator for SFRP has only recently received sparse attention; 38,39 however, the presence of an internal bisalkoxyamine linker in a macromolecule may potentially lead to interesting reversible rheological and thermal properties, such as a thermally induced reduction of the molecular weight for improved melt processability or polymer mixing. 40 In addition, triblock copolymers are potentially formed in a more facile two-step synthetic process, as opposed to conventional three-step processes.…”
Section: Introductionmentioning
confidence: 99%